2020
DOI: 10.1093/neuonc/noaa222.443
|View full text |Cite
|
Sign up to set email alerts
|

Linc-08. Increased Treatment Toxicities and Inferior Outcomes in Undernourished Children With Brain Tumours

Abstract: BACKGROUND Children on treatment for brain tumours are known to be at high risk of undernutrition, the impact on outcome and toxicity is not well understood. METHODS Retrospective audit of children(<18 years)diagnosed January 2017-December 2018 with embryonal brain tumours (medulloblastoma, primitive neuro-ectodermal tumors, pinealoblastoma, atypical teratoid/rhabdoid tumour) and treated at our centre. Data was retriev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Studies in children with acute lymphoblastic leukemia, embryonal brain tumors, and high‐risk febrile neutropenia have demonstrated poorer clinical outcomes in undernourished children 21–23 . An audit of 2110 children between 2017 and 2019 found that children with bone tumors, acute myeloid leukemia, abdominal solid tumors, and brain tumors had the highest prevalence of undernutrition at diagnosis (70%), with brain tumors continuing to lose weight while on treatment and proactive nutritional management 24 .…”
Section: Resultsmentioning
confidence: 99%
“…Studies in children with acute lymphoblastic leukemia, embryonal brain tumors, and high‐risk febrile neutropenia have demonstrated poorer clinical outcomes in undernourished children 21–23 . An audit of 2110 children between 2017 and 2019 found that children with bone tumors, acute myeloid leukemia, abdominal solid tumors, and brain tumors had the highest prevalence of undernutrition at diagnosis (70%), with brain tumors continuing to lose weight while on treatment and proactive nutritional management 24 .…”
Section: Resultsmentioning
confidence: 99%